Validation of instruments on the headmaster’s technology leadership model by using confirmatory factor analysis - Lai Chaw, Pang; Yusof, Mat Rahimi; Othman, Mohamad Khairi (International Journal of Evaluation and Research in Education (IJERE), 2024)
In 21st-century education, the role of school headmasters in technology leadership is increasingly crucial. This is due to the fact that administrators are the main force behind efforts to integrate technology in classrooms. Some headmasters resist technology use and lack understanding of its role in leadership, refraining from participating in Malaysian Ministry of Education (MoE) initiatives for technology change. To promote teachers’ integration of technology into the teaching process, headmasters need a comprehensive understanding of its implementation for both management and leadership purposes. Therefore, this study aims to assess the impact of headmasters’ technology leadership and confirm its aspects in primary schools through cross-sectional quantitative analysis. The principal technology leadership assessment (PTLA) instrument, which was given online to 516 teachers using a straight forward random selection method, served as the basis for the headmaster technology leadership questionnaire. Using IBM-SPSS-AMOS software, descriptive statistics, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) were used to evaluate the data. Six dimensions and 35 items in technology leadership are approved and validated, according to CFA results. This study successfully created an assessment model for headmasters’ technology leadership. To enhance benefits, contribute more, and address identified gaps, future researchers are encouraged to conduct larger-scale studies using both qualitative and quantitative methods.